HUBUNGAN BREASTFEEDING SELF EFFICACY TERHADAP MOTIVASI DALAM PEMBERIAN ASI EKSKLUSIF PADA IBU HAMIL PRIMIGRAVIDA - Nursari Abdul Syukur; Andi Ria Metasari; Eva Aprianty (Nusantara Hasana Journal, 2025)
Self Efficacy is the belief and confidence possessed by mothers in their ability to breastfeed their babies. Exclusive breastfeeding from 2017 tends to show the highest increase in achievement over the past 5 years. However, this achievement has not been able to reach the national target. Related to that, there is something that is unfortunate, namely the low understanding of mothers, families, and communities regarding the importance of breast milk for babies. This study aims to determine the relationship between breastfeeding self-efficacy and motivation for providing exclusive breastfeeding in primigravida pregnant women. This type of research uses analytical research with a cross-sectional method with a quantitative approach. The sampling technique is a purposive sampling technique. The instrument used is a questionnaire, then the data is analyzed univariately and bivariately with the Spearman test. The research location is the Baqa Health Center and Trauma Center with a total sample of 43 respondents. Statistical analysis using Spearman's rho with a value of p = 0.000 then p <a that the value of Asymp.Sig (2-Sided) <0.05 (0.000 <0.05) then Ho is rejected and Ha is accepted. Primigravida pregnant women with high self-efficacy will be more motivated to provide exclusive breastfeeding. High self-efficacy reflects the mother's confidence in her ability to breastfeed, which in turn increases their desire and commitment to provide exclusive breastfeeding. There is a relationship between breastfeeding self-efficacy and motivation for providing exclusive breastfeeding in primigravida pregnant women. Assessment of self-efficacy and motivation of pregnant women can be done to determine the level of mother's confidence in providing exclusive breastfeeding.